Liste over bidragsytere: Nordlit 15—Northern Minorities - Bäckström, Per; Jernsletten, Kristin; Theodorsen, Cathrine (Nordlit, 2004)
[…]
Keywords: bidragsytere; contributors; temanummer ‹Northern Minorities›; Nordlit 15